Comparison study on conventional system identification techniques - Norfadli Bin Abdul Latif (2023)
The methodology of this case study was divided into two part where the first part was to do a literature review, the purpose of this literature review to obtain a basic knowledge about the related topic and also based on research and observation the best model among the five specified models were been identified. The second part was to done a simulation using a specific software in this case was using Matlab Simulink software, with the result of the simulation a validation from the part one had been done. This thesis detailed the theory of system identification, methodology of this case study, result, discussion and conclusion.